Preparation of sulfonic acid functionalized metal organic frameworks and their application in the online solid phase extraction of parabens and sulfonamides in pre-cooked foods - Min Fang; Jianyang Ke; Zhaojie Wang; Qing Fu; Qing Yang; Lin Xu; Yuepeng Lu; Yong Yang; Xiaoming Jiang; Yongning Wu; Zhiyong Gong; Xin Liu (Food Chemistry: X)
Mixed-mode sorbents exhibit two or more primary retention mechanisms, which can enhance the selectivity and capacity of the extraction process in a single step. In this study, a facile approach was proposed to prepare functionalized metal-organic frameworks (MOFs) by post-synthetic oxidation. The composites could be varied independently for each processing step, resulting in four frameworks to meet different sample pretreatment requirements. Then, the fabricated MOFs were used as sorbents for the extraction and enrichment acidic and neutral compounds on an online solid phase extraction. The sorbents exhibited a dual retention mechanism combining hydrophilic-lipophilic balance and cation exchange interactions. Excellent linearity was observed over a range of 0.5–5000 μg kg-1 for the parabens and 10–50,000 μg kg-1 for the sulfonamides in pre-cooked foods. The detection limits were 0.02 and 1.27 μg kg-1, respectively. This method provided a novel mixed-mode framework for simultaneous determination of acidic and neutral compounds in complex samples. Keywords: Sulfonic acid functionalized metal-organic frameworksParabensSulfonamidesOnline solid phase extractionPre-cooked foods